Filling arms production data gaps: South America as a case in point - Silva, Diego Lopes da [UNESP] (Economists Peace & Security, 2018)
In this article I argue that the data collection methods and procedures behind the Stockholm International Peace Research Institute's (SIPRI) global arms trade database can also be used to approximate domestic purchases of local production of major conventional arms. The total output of domestic arms industries would then be the sum of what is domestically retained (procured) plus arms exports, if any. The feasibility of this idea is tested by presenting new data on domestic arms production for five South American countries (Argentina, Brazil, Chile, Colombia, and Venezuela) between 1960 and 2015. The results show the critical role government purchases play in maintaining domestic arms industries.